A case Report on the Estimation of Contractual Damage Caused by a Health and Rural University, South Africa - BL Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Contractual claims are mandatory for an employee who has either resigned/died or finished his or her contractual obligations. It is legally binding to an institution according to labor law. Case History: BM was such a victim who has been admired nationally and internationally but dehumanized in his own university through the process of three malicious disciplinary enquiries, two suspensions, forensic auditing, and stoppage of salary and birthday bonus. He was not allowed to go to the forensic pathology laboratory despite of the fact that he was all along a forensic pathologist. The harassment of BM became more rigorous in 2008, although he was victim long before that. The head of faculty was promoted later to a position of a university head. BM had an interest in research so he was publishing prolifically, but that disturbed the balance of the faculty staff as the rest of them contributed very little as per the report of the external assessor.1The harassment was not limited only to mental harassment but also at the same time financial losses to Mr. BM occurred. The Occupational Specific Dispensation (OSD) scale is supposed to be given to every health professional in South Africa who is working in the public sector and registered in Health Professions Council. The OSD scale started in 2009 but was not implemented for Mr. BM. Instead, Mr. BM, underwent a series of disciplinary enquiries. He was cleared all the charges and retired in 2018. The history of his research, contractual damages and other collateral losses are discussed in this report. Conclusion: There is heavy contractual damage which the Department of health and rural university has to pay from 1996 to 2018. This damage refers mainly to the short fall of salary and bonuses along with financial losses related to research.